Bottom-up Policies Trump Top-down Missions - Magnus Henrekson; Mikael Stenkula (Institute of Labor Economics (IZA), 2023)
Mission-oriented innovation policies are becoming increasingly popular among policymakers and scholars. We maintain that these policies are based on an overly mechanistic view of innovation and economic growth, suggesting that a more bottom-up approach is called for. By invoking an entrepreneurial ecosystem perspective, we point out that innovative entrepreneurship requires many other actors—besides the entrepreneur—whose skills and abilities are necessary to realize an entrepreneurial project. When mission-oriented policies play a large role in the economy, connections between actors in the ecosystem risk becoming distorted. A functioning and well-balanced entrepreneurial ecosystem requires instead an institutional framework that levels the playing field for potential entrepreneurs and encourages productive entrepreneurship. To promote this kind of system, we discuss in more detail eight key areas where appropriate horizontal or bottom-up policy measures can foster innovation and, in the end, the welfare-enhancing productive entrepreneurship policymakers and scholars strive for.
Keywords: H50; L26; O31; P16; 330; collaborative innovation bloc; entrepreneurial ecosystem; entrepreneurship policy; institutions; public choice